Standard and trace-dose lithium: A systematic review of dementia prevention and other behavioral benefits. (September 2014) - Mauer, Sivan; Vergne, Derick; Ghaemi, S Nassir
Objective: Dementia is a major public health issue, with notably high rates in persons with mood illnesses. Lithium has been shown to have considerable neuroprotective effects, even in trace or low doses. The aim of this review is to summarize the current understanding of lithium benefits in trace or low doses in dementia prevention and for other behavioral or medical benefits. Methods: A systematic review identified 24 clinical, epidemiological, and biological reports that met inclusion criteria of assessing lithium in standard or low doses for dementia or other behavioral or medical benefits. Results: Five out of seven epidemiological studies found an association between standard-dose lithium and low dementia rates. Nine out of 11 epidemiological studies, usually of drinking water sources, found an association between trace-dose lithium and low suicide/homicide/mortality and crime rates. All four small randomized clinical trials of lithium for Alzheimer's dementia have found at least some clinical or biological benefits versus placebo. Only one small randomized clinical trial (RCT) of trace lithium has been conducted, assessing mood symptoms in former substance abusers, and found benefit with lithium versus placebo. Conclusions: Lithium, in both standard and trace doses, appears to have biological benefits for dementia, suicide, and other behavioral outcomes. Further RCT research of trace lithium in dementia is warranted.